The importance of oxidative stress duration for the development of ROS-dependent apoptotic DNA degradation in cells within nerve ganglions of the mollusc Lymnaea stagnalis - Livanova, Nadezhda D.; Sidorov, Alexander V. (Experimental Biology and Biotechnology, 2025)
It was found that a two-hour exposure of isolated Lymnaea stagnalis nerve ganglia in normal Ringer’s solution containing hydrogen peroxide (1 mmol/L), a hydroxyl radical-generating mixture (0.5 mmol/L of CuCl2 and 0.5 mmol/L of ascorbate) or a combination of both, after 18 h, results in the appearance of bands of low-molecular-weight, multiple-of-180 base-pair nuclear DNA fragments in gel electrophoresis. Under mentioned above conditions, a one-hour exposure of isolated L. stagnalis central nervous system, doesn’t result in the development of apoptotic degradation of DNA from the pond snail nerve ganglions. Under conditions favourable for the generation of hydroxyl radical (in the presence of Cu2+ ions), as well as with the removal of Ca2+ ions from the environment (in zero-calcium (high-magnesium) Ringer’s solution), an increase in the number and intensity of low-molecular DNA fragment bands is observed. It is assumed that ROS-dependent apoptosis in the nervous tissue can be realised only with sufficiently prolonged oxidative stress, which allows us to consider reactive oxygen species as signalling molecules in normal physiological processes of inter- and intracellular communication within molluscan brain.